Institutional investors and firms’ cash dividend payments: evidence from non-financial firms in Indonesia - Christopher, Giovanni; Abdul Chalid, Dony (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper investigates whether an institutional presence influences the level of a firm’s cash dividend payments. Using data from all non-financial firms listed on the Indonesian Stock Exchange (IDX) during the research period of 2010 to 2015, this research performs regression analysis. The results show that institutional investors can influence cash dividend payments. However, different types of institutional investors have different impacts on dividends. While foreign investors have a significant impact on the level of dividends, local institutional investors do not have a significant effect. Also, this research reveals that free cash flow and leverage have a negative influence on cash dividend policies, while firm size, market-to-book value of equity, and return on assets have a positive influence on cash dividend policies.